Surface impedance of T1-2212 thin films at THz-frequencies - Khazan, M; Wilke, I; Stevens, C (2001)
We report on first measurements of the surface resistance and the London penetration depth of Tl2Ba2CaCu2O8 thin films in the frequency range from 200 GHz to 1.0 THz at temperatures from 25 to 268 K carried out by time-domain Terahertz transmission spectroscopy. We observe in the superconducting state an increase of the surface resistance with the square of the frequency up to 0.9THz at 77K and above. At 78K and 0.9 THz the surface resistance is 1.6 Ω. Below 77K the surface resistance increases with the cube of the frequency. Finally, the surface resistance of Tl2Ba2CaCu2O8 is compared to that of YBa2Cu3O6.95 and gold.